1, 2‐Dithiooxalato‐Bridged Heterobimetallic Complexes as Single‐Source Precursors for Ternary Metal Sulfide Semiconductors. Issue 3 (18th December 2014) - Nowotny, Mathias; Foro, Sabine; Heinschke, Silvio; Hoffmann, Rudolf C.; Schneider, Jörg J.
Abstract: The new 1, 2‐dithiooxalato‐bridged bimetallic Cu–Ga, Cu–In, and Cu–Sn complexes [(Ph3 P)2 Cu(μ‐S2 C2 O2 )3 Ga] (1 ), [(Ph3 P)2 Cu(μ‐S2 C2 O2 )3 In] (2 ), [(Ph3 P)2 Cu(μ‐S2 C2 O2 )In(S2 CNEt2 )2 ] (3 ), and [(Ph3 P)2 Cu(μ‐S2 C2 O2 )2 Sn(S2 C2 O2 )] (4 ) were prepared and spectroscopically fully characterized. The crystal structures of2 –4 are presented. Complexes3 and4 are potential molecular single‐source precursors (SSP) for the ternary semiconductors CuInS2 and Cu2 SnS3, respectively, which can be manipulated under ambient conditions. Indeed, a study of the thermal degradation of3 and4 revealed that3 affords pure nanoscaled CuInS2 (mean diameter ca. 2 nm) when the decomposition is carried out in an oleylamine solution by using a hot‐injection or arrested‐precipitation technique at temperatures well below 250 °C. In contrast, 4 decomposes under the same reaction conditions in an ambiguous manner and forms mixed binary chalcogenide phases. This can be explained by a subtle influence of the relative stability of possible Sn II and Sn IV intermediates in the case of SSP [(Ph3 P)2 Cu(μ‐S2 C2 O2 )2 Sn(S2 C2 O2 )] (4 ). Abstract : Bimetallic single‐source precursor complexes for ternary metal sulfide semiconductors are presented. The 1, 2‐dithiooxalato ligand serves as a linker, complexation site, and molcular source of sulfur in the formation of CuInS2 nanoparticles.